ORAL TRANSMUCOSAL DELIVERY: AN IN-DEPTH REVIEW OF BUCCAL PATCH FABRICATION, INNOVATIONS AND APPLICATIONS - HUANBUTTA, KAMPANART; KUMAR, TANUJ; KUMAR, SANDEEP; KHARB, VANDANA; SANGNIM, TANIKAN; SUWANPITAK, KITTIPAT; SINGH, INDERBIR (International Journal of Applied Pharmaceutics, 2026)
Mucoadhesive buccal patches have attracted considerable interest over the last decade because of their potential as a novel drug delivery system (NDDS) for several therapeutic uses. Mucoadhesive buccal patches stick to the buccal mucosa, ensuring controlled and prolonged release of drugs, thereby largely avoiding first-pass metabolism and enhancing drug bioavailability. The present paper summarizes a thorough collection of mucoadhesive buccal patches with special emphasis on design, formulation, processing, and application in drug delivery. In addition, this article emphasizes new patent research dealing with mucoadhesive buccal patches. It provides an overview of the existing patents and discusses their novelty, usefulness, and potentiality for commercialization. The all-encompassing analysis contained within this article serves to provide as an informative tool for researchers, pharmaceutical scientists, and entrepreneurs interested in the development of mucoadhesive buccal patches as a potential drug delivery system. It also stimulates future research and innovation in this field, with potential for future advancement.